2018
DOI: 10.1155/2018/4579198
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β Polymorphisms Are a Risk Factor for Chagas Disease

Abstract: Transforming growth factor β1 (TGF-β1) is an important mediator in Chagas disease. Furthermore, patients with higher TGF-β1 serum levels show a worse clinical outcome. Gene polymorphism may account for differences in cytokine production during infectious diseases. We tested whether TGFB1 polymorphisms could be associated with Chagas disease susceptibility and severity in a Brazilian population. We investigated five single-nucleotide polymorphisms (−800 G>A, −509 C>T, +10 T>C, +25 G>C, and +263 C>T). 152 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Particularly, genes encoding cytokines/chemokines involved in inflammatory and immune response have been proposed as biomarkers (Calzada et al, 2009; Torres et al, 2010; Pissetti et al, 2011; Flórez et al, 2012; Nogueira et al, 2015; Furini et al, 2016; Ferreira et al, 2018). Thus, TGF-β1 polymorphism, mainly CT and TT genotypes at position – 509 of the TGFB1 gene have been associated with the susceptibility of acquiring CD in a Brazilian population (Ferreira et al, 2018). The same genotype, in addition to the genotypes −988 C/A; −800 G/A; −10 T/C; and 263 C/T has been studied in the Colombian and Peruvian populations.…”
Section: Family Clustering Of Congenital Transmission Of T Cruzi Infmentioning
confidence: 99%
“…Particularly, genes encoding cytokines/chemokines involved in inflammatory and immune response have been proposed as biomarkers (Calzada et al, 2009; Torres et al, 2010; Pissetti et al, 2011; Flórez et al, 2012; Nogueira et al, 2015; Furini et al, 2016; Ferreira et al, 2018). Thus, TGF-β1 polymorphism, mainly CT and TT genotypes at position – 509 of the TGFB1 gene have been associated with the susceptibility of acquiring CD in a Brazilian population (Ferreira et al, 2018). The same genotype, in addition to the genotypes −988 C/A; −800 G/A; −10 T/C; and 263 C/T has been studied in the Colombian and Peruvian populations.…”
Section: Family Clustering Of Congenital Transmission Of T Cruzi Infmentioning
confidence: 99%
“…Chagas disease patients presenting more severe forms of heart disease progression have higher levels of circulating TGF-β [8, 11]. Single nucleotide polymorphisms in the TGF-β gene (-509 C<T and +10 T<C) were shown to be a risk factor for CD susceptibility, at least in the Latin American population [13,14]. Moreover, chronic chagasic patients with higher TGF-β levels present a worse clinical outcome after 10 years of follow up [15].…”
Section: Introductionmentioning
confidence: 99%
“…We also correlated the expression of different TGF-b1 alleles with the susceptibility of CD development. We demonstrated that two TGF-b1 polymorphisms, -509 C>T (rs1800469) and codon 10 T>C (rs1800470), are associated with the susceptibility to the development of the disease in Brazilian cohort (Ferreira et al, 2018). Thus, TGF-b1 is a potential serological marker with predictive value in the clinic for patients in the early stages of the disease.…”
Section: Tgf-b and Chagas Diseasementioning
confidence: 91%